2023
DOI: 10.1109/twc.2022.3217828
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Efficiency Analysis of Hybrid Relay-Reflecting Intelligent Surface-Assisted Cell-Free Massive MIMO Systems

Abstract: A cell-free (CF) massive multiple-input-multipleoutput (mMIMO) system can provide uniform spectral efficiency (SE) with simple signal processing. On the other hand, a recently introduced technology called hybrid relay-reflecting intelligent surface (HR-RIS) can customize the physical propagation environment by simultaneously reflecting and amplifying radio waves in preferred directions. Thus, it is natural that incorporating HR-RIS into CF mMIMO can be a symbiotic convergence of these two technologies for futu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…Motivated by this, the works [13] and [14] investigated the key benefits of active RIS-assisted networks in terms of secrecy improvement and throughput maximization. In addition, the authors of [15] proposed another RIS architecture enabling simultaneous signal reflection and amplification, termed hybrid relay-RIS (HR-RIS). Different from the active RIS that enables signal amplification by embedding negative resistance components into each element, HR-RIS requires expensive and powerhungry RF chains to amplify signals.…”
Section: A Related Workmentioning
confidence: 99%
“…Motivated by this, the works [13] and [14] investigated the key benefits of active RIS-assisted networks in terms of secrecy improvement and throughput maximization. In addition, the authors of [15] proposed another RIS architecture enabling simultaneous signal reflection and amplification, termed hybrid relay-RIS (HR-RIS). Different from the active RIS that enables signal amplification by embedding negative resistance components into each element, HR-RIS requires expensive and powerhungry RF chains to amplify signals.…”
Section: A Related Workmentioning
confidence: 99%
“…Simulations revealed that the proposed algorithm outperforms the benchmark algorithms that optimize one or two types of these parameters. In [18], Nguyen et al designed a hybrid Relay-RIS architecture in which a small number of passive elements are substituted with active processing units and pointed out that the proposed hybrid Relay-RIS architecture achieves a significant improvement in the SE performance over the pure passive RIS architecture at the cost of increased power consumption. Note that [15]- [18] all used the DE scheme, which minimizes the pilot overhead but degrades the accuracy of the channel estimation.…”
Section: A Related Workmentioning
confidence: 99%
“…In [18], Nguyen et al designed a hybrid Relay-RIS architecture in which a small number of passive elements are substituted with active processing units and pointed out that the proposed hybrid Relay-RIS architecture achieves a significant improvement in the SE performance over the pure passive RIS architecture at the cost of increased power consumption. Note that [15]- [18] all used the DE scheme, which minimizes the pilot overhead but degrades the accuracy of the channel estimation. Bashar et al [19] designed an ON/OFF estimation (OE) scheme that estimated the indirect RIS-assisted channel sequentially and proposed an efficient max-min SE optimization algorithm with respect to the RIS phase shifts under zero-forcing receivers.…”
Section: A Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In a UC CF-mMIMO system, each AP serves only a predefined number of UEs rather than all. Recently, in [28], authors proposed the hybrid relay-reflecting intelligent surface-assisted CF-mMIMO system where the SE for the uplink and downlink of the proposed system was analyzed. Most of the papers mentioned above derived and analyzed SE using the popular use-and-then-forget (UaTF) bound.…”
mentioning
confidence: 99%